Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.1 Exercises - Page 103: 32



Work Step by Step

$\\f(x)=\frac{6}{x+2}$ $\\f(x)=6(x+2)^{-1}$ $\\f'(x)=-6(x+2)^{-2}$ $\\f'(x)=\frac{-6}{(x+2)^{2}}$ $\\f'(0)=\frac{-6}{(0+2)^{2}}$ $\\f'(0)=\frac{-3}{2}$ Apply to straight line equation (y-y1)=m(x-x1) $\\y-3=\frac{-3}{2}x$ $\\y=\frac{-3}{2}x+3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.